Gestion policière et enfermement non pénal : la mise à distance des « fous dangereux » dans le Sénégal colonial - Romain Tiquet (Clio@Themis)
This article looks at individual cases of "dangerous lunatics" in the colony of Senegal to shed new light on the legal and logistical shortcomings of the care of the insane in the territory. The management of "dangerous lunatics" is above all a matter of police and repressive management of madness, resulting in the confinement of lunatics in a multitude of often non-medical places scattered throughout the country. Rather than thinking about the treatment of individuals, the analysis of these files reveals the permanent negotiation between various authorities of the colony. They wish above all to relieve themselves of the responsibility of receiving a "dangerous madman" and the possible danger that it may pose.